Improving the Performance of Wireless LANs: A Practical Guide - Sarkar, Nurul (Chapman & Hall/CRC computer and information science series, 2014)
While there are countless books on wireless networks, few actually quantify the key performance-limiting factors of wireless local area networks (WLANs) and describe various methods for improving WLAN performance. Fulfilling these needs, Improving the Performance of Wireless LANs: A Practical Guide provides both theoretical background and empirical